PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN IZIN TINGGAL KEIMIGRASIAN (Studi Kantor Imigrasi Kelas I Bandar Lampung) - Albert Sanusi (Universitas Lampung, 2016)
The presence of foreigners in the area of Lampung is increasing rapidly. But most foreigners are missing or doing activities that are inconsistent with the purpose of providing immigration permit. Results of research and discussion show that law enforcement criminal act of abuse of a residence permits the immigration done by administrative measures and actions pro-justice immigration. Obstacles to the enforcement of the law against the crime of abuse of a residence permit immigration because the number of immigration officers who conduct surveillance and monitoring of the presence of foreigners is still lacking, a lack of coordination and cooperation across sectors, the lack of investigators Immigration master a foreign language other than English, the limited number of facilities operational support and Lampung people that are non-cooperative which reports or complaints from the public about the existence or activities of foreigners who are nearby are very limited. Suggestions from this study are the immigration officers should increase oversight of the existence and activities of foreigners. Pro-justice in law enforcement actions should be effected, in order to ensure a deterrent effect to the perpetrators and other foreigners so as not committing a crime similar immigration. In addition, Lampung people are expected to cooperate with immigration officials to make a complaint about the existence or activities of foreigners who are nearby. Keywords: Law Enforcement, Residence Permit, Immigration